Organic charge transfer compound, crystal, preparation method and application
By using 1,2,4,5-tetracyanobenzene and benzo five-membered heterocyclic compounds to prepare organic charge transfer complexes, the problems of their photoelectric conversion stability and efficiency are solved, and a more stable and efficient photoelectric conversion effect is achieved.
Patent Information
- Application Number
- CN202411851458.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing organic charge transfer complexes have poor photoelectric conversion stability and low photoelectric conversion efficiency, which affects their luminescence characteristics.
The organic charge transfer complex was prepared by grinding method using 1,2,4,5-tetracyanobenzene as the acceptor and benzo five-membered heterocyclic compound as the donor, and its crystals were prepared by adding solvent, sealing, ventilation, and placing them at room temperature.
The stability and photoelectric conversion efficiency of the organic charge transfer complex are improved, so that it presents a different luminous color than a single component, and has a wide spectral absorption range and a higher photoelectric conversion efficiency.
Smart Images

Figure CN119685007A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of color-changing luminescent materials, and in particular to an organic charge transfer complex, a crystal, and a preparation method and application thereof. Background Art
[0002] Organic charge transfer complexes (OCTCs), as a new material with unique optoelectronic properties, have attracted extensive attention from researchers due to their great potential in organic photovoltaics (OPV), photodetectors, organic light-emitting diodes, etc. In the past three decades, organic charge transfer complexes have received extensive attention due to their characteristics in charge transport, luminescence, nonlinear optics, photoelectric conversion and external stimulation.
[0003] In recent years, with the rapid development of organic synthetic chemistry, photophysics and materials science, the research on organic charge transfer complexes has made significant progress. In terms of preparation, researchers have successfully prepared a variety of organic charge transfer complexes with excellent performance by designing new molecular structures, optimizing preparation processes and introducing new preparation technologies. In terms of performance research, researchers have conducted in-depth research on the optoelectronic properties, stability and influencing factors of organic charge transfer complexes, and have achieved a series of important results.
[0004] However, although some progress has been made in the research of organic charge transfer complexes, the existing organic charge transfer complexes have poor photoelectric conversion stability and low photoelectric conversion efficiency. Summary of the invention
[0005] The present invention provides an organic charge transfer complex, crystal, preparation method and application, which effectively solves the technical problem that the current organic charge transfer complex has poor photoelectric conversion stability and low photoelectric conversion efficiency, thereby affecting the luminescence characteristics of the complex, and at the same time provides an organic charge transfer complex with unique photoelectric properties.
[0006] The first object of the present invention is to provide a method for preparing an organic charge transfer complex, comprising the following steps:
[0007] 1,2,4,5-Tetracyanobenzene (structural formula: ) as the acceptor and a benzo five-membered heterocyclic compound as the donor, an organic charge transfer complex was obtained by a grinding method.
[0008] As a preferred embodiment, the benzo five-membered heterocyclic compound is indene (BC: ), indole (BN: ), benzofuran (BO: ) or benzothiophene (BS: ), the molar ratio of the 1,2,4,5-tetracyanobenzene to the benzo five-membered heterocyclic compound is 1:1.
[0009] As a preferred embodiment, the grinding time is 1 to 4 minutes.
[0010] The second object of the present invention is to provide an organic charge transfer complex prepared by the above preparation method.
[0011] The third object of the present invention is to provide an organic charge transfer complex crystal, which is prepared using the above-mentioned organic charge transfer complex.
[0012] The fourth object of the present invention is to provide a method for preparing the above-mentioned organic charge transfer complex crystal, comprising the following steps: adding a solvent to the organic charge transfer complex, sealing, ventilating, and placing at room temperature to obtain the organic charge transfer complex crystal.
[0013] As a preferred embodiment, the usage ratio of the organic charge transfer complex to the solvent is 0.03 g:8-15 mL.
[0014] As a preferred embodiment, the solvent is one or two of dichloromethane, ethyl acetate, methanol and tetrahydrofuran.
[0015] As a preferred embodiment, the storage time at room temperature is 1 to 2 weeks.
[0016] The fifth object of the present invention is to provide a use of the above organic charge transfer complex in preparing fluorescent materials.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention provides an organic charge transfer complex, crystal, preparation method and application. 1,2,4,5-tetracyanobenzene is used as an acceptor, a benzo five-membered heterocyclic compound is used as a donor, and a grinding method is used to obtain an organic charge transfer complex. The luminescence intensity and wavelength of the organic charge transfer complex prepared by the present invention are different from those of a single donor material and an acceptor material, indicating that the present invention has successfully prepared an organic charge transfer complex. Solid ultraviolet absorption spectroscopy proves that there is a strong charge transfer effect between the donor material and the acceptor material of the organic charge transfer complex prepared by the present invention. This charge transfer state not only changes the electronic structure of the molecule, but also gives the organic charge transfer complex unique photoelectric properties, so that it presents a different luminescence color from a single component. Through the solid molecular motion phenomenon of the donor and acceptor compounds, it can be known that the direction of organic charge transfer moves from the donor material to the acceptor material.
[0019] The organic charge transfer complex prepared by the invention also has better stability, adjustability, wider spectral absorption range and higher photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The fluorescence image changes of BC and TCNB of the present invention after grinding for 4 minutes at room temperature; wherein, the upper Daylight is a photo under a fluorescent lamp; and the lower UV on is a photo under a 365nm ultraviolet lamp.
[0021] Figure 2 The figure shows the luminescence of the donor BC, the acceptor TCNB, the BC-TCNB complex powder and the crystal under ultraviolet light, wherein A is BC, B is TCNB, C is the BC-TCNB complex powder, and D is the BC-TCNB complex crystal.
[0022] Figure 3 Figure 1 is a fluorescence image change diagram of BN and TCNB of the present invention after grinding for 4 minutes at room temperature; wherein, the upper Daylight is a photo taken under a fluorescent lamp; and the lower UV on is a photo taken under a 365nm ultraviolet lamp.
[0023] Figure 4 The figure shows the luminescence of the donor BN, the acceptor TCNB, the BN-TCNB complex powder and the crystal under ultraviolet light, wherein A is BN, B is TCNB, C is the BN-TCNB complex powder, and D is the BN-TCNB complex crystal.
[0024] Figure 5 The fluorescence image change diagram of BO and TCNB of the present invention after grinding for 4 minutes at room temperature; wherein, the upper Daylight is a photo under a fluorescent lamp; the lower UV on is a photo under a 365nm ultraviolet lamp.
[0025] Figure 6 The figure shows the luminescence of the donor BO, the acceptor TCNB, the BO-TCNB complex powder and the crystal under ultraviolet light, wherein A is BO, B is TCNB, C is the BO-TCNB complex powder, and D is the BO-TCNB complex crystal.
[0026] Figure 7 The fluorescence image change diagram of BS and TCNB of the present invention after grinding for 4 minutes at room temperature; wherein, the upper Daylight is a photo under a fluorescent lamp; the lower UV on is a photo under a 365nm ultraviolet lamp.
[0027] Figure 8This is a luminescence diagram of the donor BS, acceptor TCNB, BS-TCNB complex powder and crystal of the present invention under ultraviolet light, wherein A is BS, B is TCNB, C is BS-TCNB complex powder, and D is BS-TCNB complex crystal.
[0028] Fig. 9 The fluorescence spectra of the monomers and organic charge transfer complexes of Examples 1 to 4 of the present invention are shown in Figure a; wherein Figure a is a fluorescence spectra of TCNB, BC, and BC-TCNB; Figure b is a fluorescence spectra of TCNB, BN, and BN-TCNB; Figure c is a fluorescence spectra of TCNB, BO, and BO-TCNB; and Figure d is a fluorescence spectra of TCNB, BS, and BS-TCNB.
[0029] Fig.10 The XRD diffraction patterns of the monomers and organic charge transfer complexes of Examples 1 to 4 of the present invention; wherein, Figure a is the XRD diffraction pattern of TCNB, BC, and BC-TCNB; Figure b is the XRD diffraction pattern of TCNB, BN, and BN-TCNB; Figure c is the XRD diffraction pattern of TCNB, BO, and BO-TCNB; and Figure d is the XRD diffraction pattern of TCNB, BS, and BS-TCNB.
[0030] Fig.11 Solid UV absorption spectra of BS, TCNB and BS-TCNB cocrystal in Example 4 of the present invention.
[0031] Fig.12 FIG. 1 is a graph showing the change in fluorescence image of BC and TCNB in Example 1 of the present invention in contact with each other at room temperature.
[0032] Fig.13 This is a fluorescence image change diagram of BN and TCNB in Example 2 of the present invention in contact with each other at room temperature.
[0033] Fig.14 This is a fluorescence image change diagram of BO and TCNB in Example 3 of the present invention in contact with each other at room temperature.
[0034] Fig.15 FIG. 4 is a graph showing the change in fluorescence image of BS and TCNB in Example 4 of the present invention in contact with each other at room temperature.
[0035] Fig.16 This is a fluorescence image change diagram of BC and TCNB in Example 1 of the present invention at room temperature when they are not in contact with each other.
[0036] Fig.17 This is a fluorescence image change diagram of BN and TCNB in Example 2 of the present invention at room temperature when they are not in contact with each other.
[0037] Fig.18This is a fluorescence image change diagram of BO and TCNB in Example 3 of the present invention at room temperature when they are not in contact with each other.
[0038] Fig.19 This is a fluorescence image change diagram of the BS and TCNB of Example 4 of the present invention at room temperature when they are not in contact with each other.
[0039] Fig. 20 The irradiation diagrams of the PVA composite film prepared by the organic charge transfer complex of the present invention under fluorescent light (Daylight) and ultraviolet light (UV on), wherein A is the BC-TCNB@PVA film and B is the BO-TCNB@PVA film. DETAILED DESCRIPTION
[0040] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0041] In view of the fact that the photoelectric stability of existing organic charge transfer complexes still needs to be further improved and the photoelectric conversion efficiency is low, the present invention provides an organic charge transfer complex, crystal, preparation method and application thereof.
[0042] The technical scheme and technical effects of the present invention are described below in conjunction with embodiments.
[0043] Example 1
[0044] A method for preparing an organic charge transfer complex comprises the following steps:
[0045] Use an electronic balance to weigh 0.04 g of the acceptor 1,2,4,5-tetracyanobenzene (TCNB), and use a pipette to measure the donor indene (BC) solution according to a 1:1 molar ratio, pour it into a mortar, observe it under ultraviolet light, and grind it for 4 minutes to obtain an organic charge transfer complex, which is recorded as BC-TCNB complex. Take a photo and record it. The fluorescence image change is shown in the figure below: Figure 1 shown.
[0046] The BC-TCNB complex prepared in Example 1 is used to prepare BC-TCNB complex crystals, comprising the following steps:
[0047] Weigh 0.03g of BC-TCNB complex powder and pour it into a measuring cylinder. Add 10mL of a mixture of dichloromethane and ethyl acetate in a volume ratio of 4:1 into the measuring cylinder, put it into an ultrasonic machine for sonication to fully dissolve it. After dissolution, transfer the solution to a 25mL beaker. To prevent the sealing film from being corroded, first cover the mouth of the beaker with tin foil, and then seal it with a sealing film. Subsequently, use a capillary to punch 6-8 small holes at the seal for ventilation. Place it at room temperature for 1-2 weeks to obtain BC-TCNB complex crystals, and observe the crystal growth every day.
[0048] The grown BC-TCNB crystals were placed under a microscope to observe their colors under fluorescent light and ultraviolet light, and photographed and recorded. The luminescence images of the donor BC, the acceptor 1,2,4,5-tetracyanobenzene (TCNB), the BC-TCNB complex and the BC-TCNB complex crystals under ultraviolet light are shown in the following figure: Figure 2 shown.
[0049] Example 2
[0050] A method for preparing an organic charge transfer complex comprises the following steps:
[0051] Use an electronic balance to weigh 0.04 g of the acceptor 1,2,4,5-tetracyanobenzene (TCNB), and use a pipette to measure the donor indole (BN) solution according to a 1:1 molar ratio, pour it into a mortar, observe it under ultraviolet light, and grind it for 4 minutes to obtain an organic charge transfer complex, which is recorded as BN-TCNB complex. Take a photo and record it. The fluorescence image change is shown in the figure below: Figure 3 shown.
[0052] The BN-TCNB complex prepared in Example 2 is used to prepare a BN-TCNB complex crystal, comprising the following steps:
[0053] Weigh 0.03g of BN-TCNB complex powder, pour it into a measuring cylinder, add 10mL of dichloromethane to the measuring cylinder, put it into an ultrasonic machine for sonication, and fully dissolve it. After dissolution, transfer the solution to a 25mL beaker. To prevent the sealing film from being corroded, first cover the mouth of the beaker with tin foil, and then seal it with a sealing film. Subsequently, use a capillary to punch 6-8 small holes at the seal for ventilation, place it at room temperature for 1-2 weeks, and obtain BN-TCNB complex crystals. Observe the crystal growth every day.
[0054] The grown BN-TCNB crystals were placed under a microscope to observe their colors under fluorescent light and ultraviolet light, and photographed and recorded. The luminescence images of the donor BN, the acceptor 1,2,4,5-tetracyanobenzene (TCNB), the BN-TCNB complex and the BN-TCNB complex crystals under ultraviolet light are shown in the following figure: Figure 4 shown.
[0055] Example 3
[0056] A method for preparing an organic charge transfer complex comprises the following steps:
[0057] Use an electronic balance to weigh 0.04 g of the acceptor 1,2,4,5-tetracyanobenzene (TCNB), and use a pipette to measure the donor benzofuran (BO) solution according to a 1:1 molar ratio, pour it into a mortar, observe it under ultraviolet light, and grind it for 4 minutes to obtain an organic charge transfer complex, which is recorded as BO-TCNB complex. Take a photo and record it. The fluorescence image change is shown in the figure below: Figure 5 shown.
[0058] The BO-TCNB complex prepared in Example 3 is used to prepare BO-TCNB complex crystals, comprising the following steps:
[0059] Weigh 0.03g of BO-TCNB complex powder and pour it into a measuring cylinder. Add 10mL of a mixture of dichloromethane and methanol in a volume ratio of 4:1 to the measuring cylinder, put it into an ultrasonic machine for sonication to fully dissolve it. After dissolution, transfer the solution to a 25mL beaker. To prevent the sealing film from being corroded, first cover the mouth of the beaker with tin foil, and then seal it with a sealing film. Subsequently, use a capillary to punch 6-8 small holes at the seal for ventilation. Place it at room temperature for 1-2 weeks to obtain BO-TCNB complex crystals, and observe the crystal growth every day.
[0060] The grown BO-TCNB crystals were placed under a microscope to observe their colors under fluorescent light and ultraviolet light, and photographed and recorded. The luminescence images of the donor BO, the acceptor 1,2,4,5-tetracyanobenzene (TCNB), the BO-TCNB complex and the BO-TCNB complex crystals under ultraviolet light are shown in the following figure: Figure 6 shown.
[0061] Example 4
[0062] A method for preparing an organic charge transfer complex comprises the following steps:
[0063] Use an electronic balance to weigh 0.04 g of the acceptor 1,2,4,5-tetracyanobenzene (TCNB), and use a pipette to measure the donor benzothiophene (BS) solution according to a 1:1 molar ratio, pour it into a mortar, observe it under ultraviolet light, and grind it for 4 minutes to obtain an organic charge transfer complex, which is recorded as BS-TCNB complex. Take a photo and record it. The fluorescence image change is shown in the figure below: Figure 7 shown.
[0064] The BS-TCNB complex prepared in Example 3 is used to prepare a BS-TCNB complex crystal, comprising the following steps:
[0065] Weigh 0.03g of BS-TCNB complex powder and pour it into a measuring cylinder. Add 10mL of tetrahydrofuran solution to the measuring cylinder and put it into an ultrasonic machine for sonication to fully dissolve it. After dissolution, transfer the solution to a 25mL beaker. To prevent the sealing film from being corroded, first cover the mouth of the beaker with tin foil, and then seal it with a sealing film. Subsequently, use a capillary to punch 6-8 small holes in the seal for ventilation. Place it at room temperature for 1-2 weeks to obtain BS-TCNB complex crystals, and observe the crystal growth every day.
[0066] The grown BS-TCNB crystals were placed under a microscope to observe their colors under fluorescent light and ultraviolet light, and photographed and recorded. The luminescence images of the donor BS, the acceptor 1,2,4,5-tetracyanobenzene (TCNB), the BS-TCNB complex and the BS-TCNB complex crystals under ultraviolet light are shown in the following figure: Figure 8 shown.
[0067] Application Examples
[0068] Example 1
[0069] A method for preparing a BC-TCNB@PVA film comprises the following steps:
[0070] Weigh 1 g of PVA and dissolve it in 20 mL of deionized water, heat it at 95° C. for 2 h, and obtain a 0.05 g / mL PVA aqueous solution.
[0071] Weigh 10 mg of the BC-TCNB composite sample prepared in Example 1, measure 6 mL of PVA aqueous solution, grind in a mortar for 20 min or ultrasonically stir for 20 min, spot on a clean glass plate, and dry at 60° C. to obtain a BC-TCNB@PVA film.
[0072] Example 2
[0073] A method for preparing a BO-TCNB@PVA film comprises the following steps:
[0074] Weigh 1 g of PVA and dissolve it in 20 mL of deionized water, heat it at 95° C. for 2 h, and obtain a 0.05 g / mL PVA aqueous solution.
[0075] Weigh 10 mg of the BO-TCNB composite sample prepared in Example 3, measure 6 mL of PVA aqueous solution, grind in a mortar for 20 min or ultrasonically stir for 20 min, spot on a clean glass plate, and dry at 60° C. to obtain a BO-TCNB@PVA film.
[0076] With respect to the structures and properties of the organic charge transfer complexes and corresponding crystals prepared in Examples 1 to 4 of the present invention, the luminescent properties of the thin films of Application Example 1 and Application Example 2 were tested, and the specific process and results are as follows.
[0077] 1. Structural Characterization
[0078] 1. Fluorescence spectrum analysis
[0079] Organic charge transfer complexes are obtained by self-assembly of donors and acceptors. After grinding two different powders, the luminescent color of the product changes significantly, indicating the generation of a new substance, such as Fig. 9 As shown. Fig. 9 As shown in Figure a, the maximum emission wavelength of the single-component acceptor TCNB is 347nm, and the maximum emission wavelength of the donor BC is 403nm, and they hardly emit light under ultraviolet light. However, the maximum emission wavelength of the composite material BC-TCNB is 498nm, showing a strong blue-green emission. Compared with the fluorescence spectra of the two monomers, the fluorescence emission wavelength of the composite BC-TCNB is red-shifted, which also shows that the fluorescence of the composite comes from the joint action of two molecules, rather than the luminescence of a single substance. Fig. 9 As shown in Figure b, the maximum peak of the donor BN under 280nm excitation is 318nm, and the peak of the composite material BN-TCNB under 440nm excitation is 596nm. The luminescent color has changed compared with the single component and is orange-red. Fig. 9 As shown in Figure c, the maximum peak of the donor BO is 470nm under the excitation of 330nm, and the peak of the composite material BO-TCNB is 487nm under the excitation of 379nm. The luminescent color has also changed compared with the single component, showing blue. Fig. 9 As shown in Figure d, the maximum peak of the donor BS is 327nm under excitation at 280nm, and the peak value of the composite material BS-TCNB is 498nm under excitation at 365nm, and the luminescent color is blue-green.
[0080] By comparison, it can be seen that the luminescence intensity and color of the composite materials BC-TCNB, BN-TCNB, BO-TCNB, and BS-TCNB are different from those of the single components. Therefore, it can be explained that the acceptor TCNB and the donors BC, BN, BO, and BS are indeed obtained after grinding to obtain new organic charge transfer complexes.
[0081] Since fluorescence efficiency is an important parameter to describe the properties of fluorescent molecules, the larger the value of fluorescence efficiency, the stronger the fluorescence intensity of the substance. Therefore, this paper tested the fluorescence efficiency of monomers and complexes. As shown in Table 1, the efficiency of BO-TCNB is 25.10%, which is the highest value among the four complex materials, indicating that this complex material is the brightest and strongest among the four; the efficiency of BN-TCNB is 0.50%, which is the lowest value among the four complex materials, indicating that its brightness is very weak and almost no light is emitted.
[0082] Table 1 Fluorescence efficiency of single component and composite materials at room temperature
[0083]
[0084]
[0085] 2. XRD spectrum analysis
[0086] To further demonstrate the formation of organic charge transfer complexes, e.g. Fig.10 As shown, four groups of single-component and dual-component materials were characterized by XRD. Fig.10 It can be observed that the diffraction peaks of the BC-TCNB composite powder and its crystals are significantly different from those of the individual TCNB and BC materials. This shows that the BC-TCNB composite is not just a simple doping produced by physical grinding, but a true composite eutectic. This eutectic forms an ordered and tightly packed structure through intermolecular interactions, which gives it a strong diffraction peak characteristic. Similarly, the powders and crystals of the composites BN-TCNB, BO-TCNB, and BS-TCNB are also the same as those of the single-component TCNB and BN, BO, and BS.
[0087] 3. Charge transfer properties
[0088] The charge transfer characteristics of the eutectic are very important for understanding the luminescence behavior of the eutectic. Therefore, the present invention studies the charge transfer characteristics of the prepared BS-TCNB eutectic. First, the solid ultraviolet spectrum test technology was used to measure the monomer BS, TCNB and BS-TCNB eutectic powder. By comparison, it was found that Fig.11 As shown in the figure, compared with the absorption spectrum of the monomer material in the range of about 300-360nm, the BS-TCNB co-crystal has a significant red-shifted broad peak at 420nm. This result clearly shows that the BS-TCNB co-crystal we prepared has a small band gap and there is a charge transfer effect between the donor and acceptor molecules inside the co-crystal.
[0089] 4. Visualization of solid molecular motion
[0090] During the mechanochromic phenomenon, it was found that the receptor TCNB and the donors BC, BN, BO, and BS reacted and changed color as soon as they came into contact in the agate mortar. Therefore, this phenomenon was verified.
[0091] The single-component BC and TCNB were placed in the same mortar and slowly brought into contact. The color of the luminescence at the interface changed at the moment of contact. As time went by, the range of the blue-green light gradually expanded, and the intensity of the luminescence became brighter and brighter. At about 145 seconds, the TCNB completely changed color. Taking photos from the beginning of contact and taking photos at regular intervals, it can be found that the two can also react without the action of force, and the color of the composite BC-TCNB appears blue-green under ultraviolet light, such as Fig.12 shown.
[0092] Similarly, when single-component BN and TCNB are placed in the same mortar, the color at the interface begins to change after about 1 minute of contact, and the color of the composite BN-TCNB appears orange-red under ultraviolet light. As time goes by, the orange-red color range gradually expands, but the luminescence intensity becomes dimmer and dimmer. At about 34 minutes, TCNB almost completely changes color, as shown in Figure 2. Fig.13 shown.
[0093] When the single-component BO and TCNB are placed in the same mortar, the color of the interface changes immediately at the moment of contact. Under ultraviolet light, the color of the composite BO-TCNB appears blue. As time goes by, the blue color range gradually expands and the luminescence intensity becomes brighter and brighter. At about 145s, TCNB almost completely changes color, as shown in Figure 1. Fig.14 shown.
[0094] Similarly, when the single-component BS and TCNB are placed in the same mortar, it can be seen that the interface begins to change color at the moment of contact. Under ultraviolet light, the color of the composite BS-TCNB is blue-green. As time changes, the blue-green color range gradually expands, and the luminescence intensity becomes brighter and brighter. At about 240s, TCNB almost completely changes color, as shown in Figure 2. Fig.15 shown.
[0095] During the contact color change phenomenon, it was found that the acceptor TCNB and the donors BC, BN, BO, and BS were placed on different sides of the agate mortar without contact. In order to further study the motion of solid molecules, the single component BC and TCNB were placed on different sides of the same mortar without contact. The agate mortar was sealed with a sealing film to allow the molecules to diffuse in a closed space, resulting in a complete reaction of TCNB.
[0096] from Fig.16It can be seen that there is no obvious change at 0s, and the color changes at about 6min. The left TCNB starts to turn blue-green from the side close to BC. As time changes, the blue-green color range gradually expands, and the luminescence intensity becomes brighter and brighter. At about 84min, the TCNB completely changes color. Therefore, it can be found that the direction of solid molecule movement is from donor to receptor, causing the receptor to change color.
[0097] Similarly, from Fig.17 It can be seen that there is no obvious change at 0s, and the color change begins at about 8min. The left TCNB starts to turn orange-red from the side close to BN. As time changes, the orange-red color range gradually expands, but the luminous intensity becomes dimmer and dimmer. At about 112min, the TCNB completely changes color.
[0098] from Fig.18 It can be seen that there is no obvious change at 0s, and the color changes begin to occur around 5min. The left TCNB starts to turn blue from the side close to BO. As time changes, the blue color range gradually expands, and the luminous intensity becomes brighter and brighter. At around 70min, the TCNB completely changes color.
[0099] Similarly, if Fig.19 As shown, there is no obvious change in TCNB at 0s, and the color changes at around 7min. The left TCNB starts to turn blue-green from the side close to BS. As time changes, the blue-green color range gradually expands, and the luminous intensity becomes brighter and brighter. At around 98min, the TCNB completely changes color.
[0100] 2. Application
[0101] It is worth noting that compared with the eutectic of the composite material, the formed uniform PVA film shows similar optical properties, such as BC-TCNB is yellow under fluorescent light and blue-green under ultraviolet light; BO-TCNB is yellow under fluorescent light and blue under ultraviolet light. At the same time, the obtained BC-TCNB@PVA film and BO-TCNB@PVA film have the characteristics of transparency and flexibility. Specifically, this luminescent film can be bent or folded freely. Due to the excellent flexibility and luminescent properties of BC-TCNB@PVA film and BO-TCNB@PVA film, blue-green luminescent windmills and blue luminescent paper cranes were prepared. The results show that it has great application potential in the field of luminescent crafts and has potential application value in the fields of flexible electronics, anti-counterfeiting encryption, etc. Fig. 20 As shown, the luminescent colors of BC-TCNB@PVA film and BO-TCNB@PVA film under fluorescent light and ultraviolet light respectively.
[0102] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing an organic charge transfer complex, characterized in that: The following steps are involved: An organic charge transfer complex is obtained by using 1,2,4,5-tetracyanobenzene as an acceptor and a benzo-pentacyclic heterocyclic compound as a donor through a grinding method.
2. The preparation method according to claim 1, characterized in that: The benzo five-membered heterocyclic compound is indene, indole, benzofuran or benzothiophene, and the molar ratio of the 1,2,4,5-tetracyanobenzene to the benzo five-membered heterocyclic compound is 1:
1.
3. The preparation method according to claim 1, characterized in that: The grinding time is 1 to 4 minutes.
4. An organic charge transfer complex prepared by the preparation method according to any one of claims 1 to 3.
5. An organic charge transfer complex crystal, characterized in that: The organic charge transfer complex according to claim 4 is used for preparation.
6. A method for preparing the organic charge transfer complex crystal according to claim 5, characterized in that: The method comprises the following steps: adding a solvent into the organic charge transfer complex, sealing, ventilating, and placing at room temperature to obtain an organic charge transfer complex crystal. 7 . The preparation method according to claim 6 , wherein the ratio of the organic charge transfer complex to the solvent is 0.03 g: 8 to 15 mL.
8. The preparation method according to claim 6, characterized in that: The solvent is one or two of dichloromethane, ethyl acetate, methanol and tetrahydrofuran.
9. The preparation method according to claim 6, characterized in that: The storage time at room temperature is 1 to 2 weeks.
10. Use of the organic charge transfer complex according to claim 4 in preparing fluorescent materials.
Citation Information
Patent Citations
9-acetyl anthracene eutectic material with adjustable up-conversion luminescence and preparation method thereof
CN105219375A
Organic eutectic-based electrochemical luminophor design and synthesis method
CN115096966A
Organic eutectic TCNB-TODI as well as preparation method and application thereof
CN118580160A
Organic eutectic TCNB-TMB and preparation method and application thereof
CN118812370A
Organic micro-nano eutectic material, preparation method and application
CN119039971A